MAXIMIZING THE EFFECTIVENESS OF SOCIAL MEDIA FOR EVENT MARKETING (Study Case: XYZ Business Fair) - Prameshti, Delifaysa Dyah; Cahyaningratri, Cahyaningratri (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The XYZ Business Fair is an event organized by X’s to bridge between the Netherlands and Ghana in the Business, Agriculture, Healthcare, Real Estate, and Renewable Energy sectors. Since 2018, the XYZ Business Fair has used social media to market and promote its event. The purpose of this research is to thoroughly analyze potential strategies that the XYZ business fair may employ to optimize the efficacy of social media in enhancing brand recognition and expanding the reach and engagement of prospective or past participants. This study provides an overview of the backdrop, theoretical framework, participant characteristics, and the utilization of social media for event marketing. The research findings are recommended, providing valuable insights for future events. The research findings indicate that social media platforms have established protocols for optimizing their usage, hence maximizing their effectiveness and efficiency. The organizers of the XYZ Business Fair should carefully consider the strategic approach they wish to use for utilizing social media. Additionally, numerous methods exist for effectively managing and sustaining a social media presence.